Effects of physical exercise on beta cells of the pancreas: a systematic review - Filho, Edson Meneses da Silva; Albuquerque, Jéssica Andrade de; Cacho, Roberta de Oliveira; Freitas, Rodrigo Pegado de Abreu (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Diabetes mellitus is a chronic disease that is rising in many parts of the world causing damage to functionality, quality of life and public health system. Objective: Verify the effects of physical exercise on beta cells of the pancreas in diabetic subjects. Methods: The database Cochrane Library via Wiley – CENTRAL, Pubmed, LILACS, SCIELO, Web of Science, Scopus, CINAHL were used to search the articles. The descriptors and synonyms of this topic were used in the search strategy. Controlled randomized clinical trials and quasi-randomized studies, which included in their samples diabetic humans undergone any type of physical exercise were included. The Cochrane collaboration bias risk tool was used to assess the risk of bias. Results: A total of 3.133 articles were initially identified and after reading the titles/abstracts and the full text 6 articles were selected for the qualitative evaluation. Most of the studies showed positive results of physical exercise on pancreatic beta cells, insulin secretion, insulin resistance and insulin sensitivity. The main limitations were the number of studies, few, and their methodological qualities. Conclusions: Physical exercises have beneficial effects on pancreatic beta cells, insulin resistance and insulin sensitivity; however better studies designs, with fewer biases and larger samples are needed so that the results presented do not be overestimated. This review is recorded in the Prospective Register of Systematic Reviews with registration number 42017054213